Trends and State of Research on Tourist Routes. A Bibliometric and Narrative Analysis of Literature - Vieira Salazar, Jaime Andrés; Echeverri Rubio, Alejandro; Rico Martínez, Juley Mireya (Sociedad y Economía, 2025)
Tourist routes are one of the essential elements in the world of tourism. From historical and cultural itineraries to adventure routes and ecotourism, each route offers a series of attractions that allow travelers to discover new destinations and enjoy exciting activities. Despite the extensive literature, offerings, and documentation on tourist routes, there is a lack of comprehensive and up-to-date bibliometric studies that account for the intellectual structure of knowledge and research trends through the use of data analytics tools. The methodology employed used 407 documents available in the Web of Science and Scopus databases to develop a scientific mapping and construct a theoretical framework, in the form of a literary narrative, based on the Tree of Science algorithm. Among the main findings are the research trends in tourist routes, identifying three thematic clusters related to tourism planning, sustainable tourism, and cultural tourism.